PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBASIS LESSON STUDY DALAM MENINGKATKAN KUALITAS PEMBELAJARAN FISIKA DI SMP NEGERI KOTA PADANG - Murtiani, Murtiani; Fauzan, Ahmad; Ratnawulan, Ratnawulan (Jurnal Penelitian Pembelajaran Fisika, 2012)
The cause of the low activity of the students in learning Physics in Public Junior High School in Padang,due to the students feel that Physics is not an interesting subject and unrelated to the real world application. These factors have impacts towards the student’s learning activities in Physics, their achievement in Physics, and the student’s learning quality in Physics. One solution to overcome these problems is by applying the Contextual Teaching and Learning (CTL)–Lesson Study–Based Approach. This research aims at elaborating the CTL–Lesson Study–Based Approach to enhance the student’s learning activity in Physics, and the student’s achievement in Physics, either the students have low, medium or high intelligence level. This type of research is a combined quantitative and qualitative. This research took place in public junior high schools in Padang on first semester of academic year 2009/2010. The samples for this research were the students in class VII-4 at SMPN 17 Padang, students in class VII-5 at SMPN 7 Padang and students in class VII-B at SMPN 8 Padang. The data were collected through observation, interview, questionnaire and video recording by some observers during the learning process takes place as well as through examination given to the students. The data were analyzed using descriptive quantitative and qualitative.       The result of data analysis indicates that the implementation of the CTL–Lesson Study–Based Approach can improve the student’s learning activity in Physics, and the student’s achievement toward Physics for the case of school with students with low and moderate intelligence level. While in the school where the student’s intelligence level is high, the improvements occur only on the student’s achievement in Physics. It can be concluded that the CTL–Lesson Study–Based Approach can improve the student’s learning activities in Physics, and also the student’s achievement in Physics. Therefore, the CTL–Lesson Study–Based Approach can enhance the learning quality in Physics.   *):  Jurusan Fisika **): Jurusan Matematika